(untitled) (Journal of Bangladesh Academy of Sciences, 2014)
In this paper several features of fuzzy compactness to established fuzzy analogues of wellknown theorems on (usual) compact topological spaces have been described. DOI: http://dx.doi.org/10.3329/jbas.v38i2.21334 Journal of Bangladesh Academy of Sciences, Vol. 38, No. 2, 111-117, 2014